COVID-19: Fatores associados a recusa ou adesão da vacina entre lactantes - Gomes, Laryssa Martins (2024)
Introduction: The public health crisis caused by the SARS-CoV-2 virus has profoundly affected people of all ages, including pregnant and postpartum women. The rapid development of vaccines was crucial in containing the spread of the virus, but it also raised concerns regarding their safety. Vaccine hesitancy has emerged as a serious public health issue, and the global disparity in vaccine acceptance has been a continuous source of concern for health authorities. Objective: To describe the factors associated with the refusal or acceptance of COVID-19 vaccines among breastfeeding women. Material and Methods: A systematic review study (registration no. CRD42023358812) was conducted following the guidelines of the Joanna Briggs Institute (JBI), using the databases PubMed, CINAHL, SCOPUS, EMBASE, and Web of Science. Prospective or retrospective observational studies investigating breastfeeding women, vaccination against SARS-CoV-2, and related outcomes were selected, following the Population, Exposure, Comparison, Outcome, and Study design (PECOS) strategy. Studies published from 2020 in Portuguese, English, and Spanish were included. The selection of studies was conducted by two independent researchers using the Rayyan tool, followed by methodological quality assessment, risk of bias evaluation, and data extraction. Results: Initially, 612 studies were identified. After the removal of duplicates and exclusions based on eligibility criteria, 17 articles were included in the review. Factors associated with vaccine refusal among breastfeeding women include concerns about possible harm to the infant, risks of infection and side effects, lack of scientific data and information about the vaccine, as well as perceptions of ineffectiveness and insecurity. In contrast, factors that promoted greater vaccine acceptance included fear of infection and severe symptoms, as well as the protection of the infant. The influence of health professionals and family members was crucial for both refusal and acceptance of vaccination. Conclusions: Fear of infection, side effects, and concern for the health of their children are associated with both vaccine refusal and acceptance, highlighting the impact of risk perceptions on the vaccination behavior of these women. The distinction between the lack of clear information, which contributes to hesitancy, and the confidence in vaccine safety, which promotes acceptance, underscores the importance of health communication, combating misinformation, and strengthening trust in health authorities and science. The crucial role played by health professionals and family members in encouraging or discouraging vaccination reinforces the need for targeted interventions for these groups, given their significant impact on vaccination decisions. Understanding these factors is essential for developing effective strategies that promote vaccine acceptance and public health.